Komunikasi Internal dan Keterlibatan Karyawan: Tinjauan Literatur yang Sistematis di Seluruh Sektor: Penelitian - Muhammad Faisal (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
between internal communication and employee engagement across sectors. Although interest in the topic is growing, research remains fragmented across industries and regions. A Systematic Literature Review (SLR) analyzed 45 peer-reviewed articles published between 2010 and 2024, sourced from Scopus, Web of Science, Google Scholar, and EBSCO, using the keywords “internal communication” and “employee engagement.” The selection process followed the PRISMA protocol. Findings revealed three main themes: (1) communication channels and media effectiveness, (2) the communicative role of leadership in driving engagement, and (3) the influence of organizational culture. The private sector emphasized digital and strategic communication, while the public and nonprofit sectors favored value-driven and participatory approaches. Most studies originated from North America and Europe, with emerging contributions from Asia. The review is limited to English-language publications and excludes gray literature. Future research should explore engagement mechanisms through cross-cultural and cross-sectoral comparisons. The findings offer strategic insights for HR professionals in designing internal communication frameworks, particularly in hybrid and multicultural work environments. This study provides a comprehensive cross-sectoral synthesis, highlighting trends, gaps, and future research directions.